Bilateral Transverse Sinus Angioplasty for the Treatment of Idiopathic Intracranial Hypertension – Case Report and Literature Review - Manzato, Luciano B.; Mesquita Filho, Paulo Moacir; Frighetto, Leonardo; Azambuja, Nério Dutra, Jr.; Cordeiro, Rafael; Vanzin, José Ricardo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Idiopathic intracranial hypertension (IIH) is a disease characterized by an increase in intracranial pressure, without presence of parenchymal lesions or hydrocephalus that justify it. Over 90% of cases there is association with stenosis of the dural venous sinuses. It is characterized by headache, tinidus, nausea, vomiting and visual disturbances. Initial treatment is clinical and when it fails there is indication of invasive procedures, among them shunts and fenestration of the optic nerve sheath. Angioplasty of dural venous sinuses, when indicated, has shown an alternative with better results and less complications. We report a case of a female patient, with 27 years old, diagnosed with IIH and bilateral transverse sinus stenosis, which was treated by bilateral stenting and total resolution of symptoms. Besides describing the case we review the literature about the subject.
Keywords: intracranial hypertension; angioplasty; venous sinus stenosis